ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI UNTUK MEMBAYAR PAJAK DENGAN KONDISI KEUANGAN DAN PREFERENSI RISIKO WAJIB PAJAK SEBAGAI VARIABEL MODERATING (Studi Kasus pada Wajib Pajak yang Terdaftar di KPP Pratama Candisari - Murni Julianti; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2014)
This research aims to analyze the factors that infuence the compliance of individual taxpayers to pay taxes. This is a replication from Alabede’s research in 2011 in Nigeria, but one variable is added in this research. We add taxpayer’s knowledge about tax laws as an independent variable. This research is also use financial condition and risk preferences of taxpayers as moderating variable. Data were collected by survei to taxpayers listed in the Primary Tax Office Candisari Semarang. Statistical tests were perfomed using Moderating test of regression. Statistic program in this research used SPSS 19. The results of this research indicated that the perception of taxpayers on tax service quality and taxpayers knowledge of tax laws have positive effect on taxpayers compliance. Financial condition and risk preferences of taxpayers also have role as pure moderator which strengthen or weaken the relationship between the dependent variable with the independent variables. Implication of this research showed that taxpayer’s compliance in Indonesia was low. Socialization was needed to increase the taxpayer’s compliance. The socilization can be done through advertising on television, radio and newspaper. Direktorat Jenderal Pajak also need to regularly hold events that educated and entertain the taxpayer to have the willingness to pay their taxes.